Pola Komunikasi Jarak Jauh antara Anak dan Orang Tua dalam Menjaga Hubungan Keluarga: Studi pada Mahasiswa FISIP UNSIKA Angkatan 2019 yang Berasal dari Luar Karawang - Putri, Inneke; Tayo, Yanti; Fitriana Poerana, Ana (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Communication patterns in the family are the key to maintaining good relationships between parents and children. Lack of communication intensity during long distance relationships makes communication less effective. Therefore, researchers want to research how long-distance communication patterns between children and parents maintain family relationships. This research aims to find out how long-distance communication patterns between children and parents maintain family relationships (Study of 2019 FISIP UNSIKA Students from Outside Karawang). The research method used in this research is descriptive qualitative. The results of this research can be concluded that the communication patterns used by the six informants between children and parents when having long distance relationships are liberating, authoritarian and democratic communication patterns. Researchers also link the interaction approach theory, which in this theory has 4 assumptions used in maintaining long distance relationships. When communicating long distance, these six informants apply primary and secondary communication patterns. This can be seen from the results of research with the six informants that they communicate using verbal symbols, namely in the form of language, to express words, and chat via telephone and using the WhatsApp chat feature and media. video calls. The obstacles experienced in the process of communicating long distances include time, physical and economic barriers